COMPARISON OF ARTICULATING PAPER MARKINGS AND T SCAN RECORDINGS FOR OCCLUSAL POINTS EVALUATION AMONG NORMAL DENTULOUS POPULATION - B., Sadhvi; V., Suresh; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Articulating paper is a diagnostic tool used in dentistry to highlight occlusal contacts and the distribution of occlusal forces. That is, it marks those points on the teeth where the teeth contact during biting and grinding. T-Scan is an objective assessment tool used to evaluate the occlusion of a patient. Unlike articulating paper, which can only determine location, T-Scan can identify both force and timing, two of the most fundamental parameters for measuring occlusion. The aim of this study is to compare the articulating paper markings and T scan recordings for occlusal point evaluation among normal dentulous populations. The articulating paper was placed intraorally, and the subject was asked to clench their teeth firmly on the articulation paper. Standardized photographs were taken using an intraoral mirror to compare the markings with those T-Scan III multi-bite recordings at a later stage. The subjects were asked to occlude into and through the recording sensor and hold their teeth firmly intercepted together for 1–2 s The procedure was repeated three times, and the average of three recordings was taken. A questionnaire was then prepared on the comparison of both the above and circulated among dental practitioners and the results were statistically analysed. Close to 90% use articulating paper post-FPD insertion, whereas only 36% use it for post-orthodontic procedures. Close to 66% of them had doubts on how to use the articulating paper to its fullest purpose and also were not clear about the thickness of the same. Some felt red is thicker than blue or a certain colour is for static occlusion and others for movements. Many of them were able to correlate between articulating paper and the T scan contact points but couldn’t accurately correlate the light and the heavy contacts, difficulties faced were patient cooperation, salivary contamination, and tears. Many felt use of TScan was advantageous, but for clinical correlation, dentists prefer articulating paper. Area to be emphasised is the post-orthodontic corrections using articulating paper, which, in the present study, is not prevalent.